KAJIAN PENGEMBANGAN OBJEK AGROWISATA KACINAMBUNAN HIGHLAND PUNCAK 2000 SIOSAR KECAMATAN TIGAPANAH KABUPATEN KARO - Adi Permana Sinuhaji; Fonny Rewah; Kalvin Salindeho Andaria (GEOGRAPHIA : Jurnal Pendidikan dan Penelitian Geografi, 2021)
The tourism sector today still relies on the use of coastal areas as objects. There needs to be a tourist attraction so that it is more diverse. The tourism sector is also expected to encourage other sectors such as the plantation, agriculture, trade, and industrial sectors. While in the agricultural sector is agro-tourism. Therefore, it is necessary to study the development of agro-tourism objects, especially Agro-tourism in the Kacinambun Highlands, Puncak 2000, Siosar, Kacinambun Village, Tigapanah District, Karo Regency, North Sumatra. The focus of the research is the study of development factors with sub-focuses, namely: 1) attractiveness conditions, 2) accessibility conditions, 3) facilities and infrastructure conditions, 3) promotion conditions, and 4) visiting conditions. The research method used is descriptive qualitative. The results of the study show, 1) the attraction is the beautiful nature offered by the charm and views of the community's plantations, 2) easy accessibility, positioning strategies, transportation networks are still minimal, 3) facilities and infrastructure are already supportive and available both complementary infrastructure, supporting infrastructure, and public infrastructure but not yet maximized. 4) tourism promotion utilizes social media, magazines, and daily newspapers to provide information to potential tourists, and 5) efforts to increase visits are carried out by developing attractions, facilities and also utilizing natural beauty such as community agricultural plants with multicultural types of plants to be shown to tourists.